Badi didi. - CHATTOPADHYAY (Sharatchandra). 9 (Dilli Prabhat Prakashan, 1967)
Badi Didi is the first novel written by Sarat Chandra Chattopadhyay--one of the most popular Bengali writers of all time, the creator of iconic works such as Devdas and Parineeta. Madhavi, affectionately called Badi Didi (elder sister), is a widow. The society she lives in dictates that it is downright wrong for a woman to even think of being with another man after her husband's death. She had no intention of marrying again . . . and then, Surendranath entered her life.The son of a zamindar, Surendranath has come to tutor Madhavi's younger sister. And it takes him no time to fall for the beautiful Madhavi. And despite not wanting to, Madhavi realizes that she is falling for him, too.Will Madhavi dare to flout social convention and be with another man, even though she is a widow? Or will she be forced to stifle her wishes and live a lonely life?